2013
DOI: 10.7314/apjcp.2013.14.10.5671
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of BRCA1 and BRCA2 Variants with Breast Cancer in an Ethnic Population of Saudi Arabia, an Emerging High-Risk Area

Abstract: Incidence of breast cancer shows geographical variation, even within areas of ethnic homogeneity. Saudi Arabia has witnessed an increase in occurrence of breast cancer in its unexplored ethnic populations over the past few years. We aimed at determining whether any association exists between single nucleotide polymorphisms in breast cancer associated gene 1 (BRCA1) and breast cancer associated gene 2 (BRCA2) and the risk of breast cancer. TaqMan based Real Time Polymerase chain reaction genotyping assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…And detailed characteristics of these studies were presented in Table 1. The distribution of genotypes in the controls was in agreement with HWE for all except for one study (P = 0.005) [22], and omission of this individual study did not change the result substantially (data not shown).…”
Section: Characteristics Of the Studiessupporting
confidence: 63%
See 1 more Smart Citation
“…And detailed characteristics of these studies were presented in Table 1. The distribution of genotypes in the controls was in agreement with HWE for all except for one study (P = 0.005) [22], and omission of this individual study did not change the result substantially (data not shown).…”
Section: Characteristics Of the Studiessupporting
confidence: 63%
“…1). Finally, a total of 8 case-control articles met our inclusion criteria [15][16][17][18][19][20][21][22], including 19,878 subjects. And detailed characteristics of these studies were presented in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In addition, it was demonstrated that the BRCA1 polymorphism, rs799917, was associated with breast cancer risk (18). By contrast, Hasan et al (19) reported that rs799917 demonstrated no significant association with breast cancer in 100 patients with breast cancer in Saudi Arabia (19). Therefore, the role of genetic variants in the BRCA1 3'UTR and its post-transcriptional regulation remains unclear.…”
mentioning
confidence: 97%
“…Therefore, the role of genetic variants in the BRCA1 3'UTR and its post-transcriptional regulation remains unclear. Such differences may be due to reproductive patterns, in addition to exposure to particular environmental carcinogens, different lifestyles and different genetic backgrounds (19). The present study focused on the polymorphisms in the BRCA1 3'UTR, and identified that rs12516 and rs8176318 had potential miRNA binding sites.…”
mentioning
confidence: 99%
“…Our results were intermediate between Sirisabya et al (2007), who found no correlation between the BRCA1 expression and any of the clinicopathological variables, and Werness et al (2004), who detected fewer grade 1 and stage I cancers in BRCA1 positive patients than in BRCA1 negative patients. Similarly, polymorphisms of breast cancer susceptibility gene BRCA1 had no statistically significant correlation with clinicopathological characteristics of breast cancer in Saudi population (Hasan et al, 2013). In addition, Lan et al (2013) observed no significant differences in the methylation frequencies of BRCA1 between stages and ages of ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 95%